Deployment Strategy and Dynamic Analysis of Large Ring Truss Antenna - Jiang Zhao; Jungang Yang; Yong Xiao; Xiaofei Ma (International Journal of Aerospace Engineering)
The deployment strategy and dynamic analysis of the AM-2 AstroMesh ring truss antenna reflector are studied in this paper. The rigid multibody dynamic models of the truss structures with alterable and fixed diagonal length are established, respectively, by using the natural coordinate formulation (NCF). The driving scheme and the synchronous constraint scheme are proposed for two types of truss structure, respectively. The degree of freedom (DOF) analysis of the truss structure is carried out according to the redundant constraint processing method. The deployment strategies of the two different types of truss structures are discussed. The dynamic simulation of the deployment of a 30-side AM-2 AstroMesh reflector truss structure with fixed diagonal length without gravity is carried out. The deployment characteristics of the truss structure are obtained. The driving forces are predicted according to the dynamic simulation.